A Criminal Law Review of Social Media Advertisements Leading to Gambling and Illegal Activities in Indonesia - Amalia, Dinda; Toteles, Aris; .Bangas, Karlinae D. (Dinasti Research, 2025)
This research discusses the criminal law perspective on social media advertisements that lead to gambling and illegal activities in Indonesia. The development of information and communication technology has facilitated the spread of illegal advertisements, including online gambling, through social media platforms. Although gambling is prohibited under Article 303 of the Indonesian Criminal Code (KUHP) and Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE), this practice remains prevalent with increasingly sophisticated marketing strategies, such as the use of influencers and referral codes. This research employs a normative juridical method to analyze the effectiveness of existing regulations, challenges in law enforcement, and effective criminal liability models. The findings indicate that while regulations provide a strong legal foundation, their implementation faces obstacles, such as difficulties in identifying perpetrators, low legal awareness among the public, and limited law enforcement resources. Therefore, this research recommends regulatory revisions, enhanced law enforcement capacity, and public education to more effectively address this phenomenon